Mental Health Status of Secondary Level School Students of Gorkha District - Karakheti, Ashwin; Mahato, Namra Kumar; Chaudhary, Roshan Kumar; Sapkota, Biswash; Tiwari, Sansar Babu; Khadka, Pratiksha; Karakheti, Arati (Nepal Journal of Health Sciences, 2022)
Introduction: Mental health problem among the adolescent is one of the major global challenges. Adolescence is a transition phase ranging from 10 to 19 years. Most of these problems are manifested at this stage of life. Adolescents are more vulnerable to mental health problems as they face biological, physical, social and cultural transition simultaneously. Objective: The study objective of this study is to assess mental health status among secondary level school adolescents. Methods: This study is a cross-sectional study conducted among 317 secondary level school students of Gorkha, Nepal. Structured self-administered questionnaire and General Health Questionnaire-28 (GHQ-28) were used. Data was entered in Epidata and analyzed in SPSS 11.5 Results: In this study, 24.9% of the respondents were found to have mental health problems. The mean age of respondent was 16.47 ± 1.32 years. In the study female respondents and adolescents from community school were more likely to develop mental health problems. Conclusions: Mental Health problem among secondary level school going adolescents was in alarming situation. Thus, to improve this problem among adolescents a comprehensive effort needs to be initiated.